Comparison of Two High-End Ultrasound Systems for Contrast-Enhanced Ultrasound Quantification of Mural Microvascularity in Crohn’s Disease - Zink, F.; Kratzer, W.; Schmidt, S.; Oeztuerk, S.; Mason, R. A.; Porzner, M.; Klaus, J.; Haenle, M. M.; Graeter, T. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
Purpose: To verify the reproducibility of contrast-enhanced ultrasound (CEUS) quantification results of two different high-end ultrasound systems and to evaluate the clinical utility of the method in patients with Crohn’s disease (CD).Materials and Methods: 18 patients with histologically confirmed CD (36.8 % women, 63.2 % men; mean age 43.7 ± 14.1 years) and wall segments thicker than 5 mm were recruited. CEUS quantification and conventional ultrasound investigation were performed under standardized settings using Toshiba Aplio500 and Siemens Acuson S3000 high-end ultrasound systems. CEUS was performed at a low mechanical index of 0.1 after bolus application of 4.8 ml of SonoVue® contrast medium. The recorded DICOM clips were quantified using VueBox® (version 4.3) calculating 11 quantitative parameters. Subsequently, CEUS quantification and conventional ultrasound results were analyzed.Results: Correlation of quantitative parameters between the Aplio500 and AcusonS3000 systems for peak enhancement (PE), rise time (RT), wash-in-rate (WiR) and quality of fit (QOF) yielded significance levels of p < 0.05 and p < 0.0001 for wash-in-wash-out area under the curve (WiWoAUC). Spearman rank test showed moderate levels of correlation for PE, RT, WiR and QOF (r = 0.5, 0.49, 0.49 and 0.5 respectively), and high correlation for WiWoAUC (r = 0.89) between the two ultrasound systems.Conclusion: Due to multiple uncontrollable affecting factors, the method of CEUS quantification by VueBox in the intestine cannot be recommended for device-independent multicenter studies. Therefore we suggest to use identical ultrasound systems and probes as well as to establish adequate reference ROIS, like a AIF-ROI.
Keywords: Crohn's disease; CEUS quantification; contrast agents; utrasonography